Badanie środowiska medycznego na temat poziomu świadomości praw pacjenta - Banaś, Joanna; Machowska-Szewczyk, Małgorzata (Analysis of Level of Awareness of Patient's Rights in Medical Community, 2008)
The classification of medical care workers in the Province of Western Pomerania based on the GDM generalized distance measure is presented. The survey concerning respecting children's rights by nurses was conducted in 2002. The global awareness level concerning the problem of respecting children's rights is determined on the grounds of awareness correlates and case analysis. The classification is analyzed with respect to differentiating factors (age, practice, education, place of work).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 323-329